2012
DOI: 10.1890/es11-00345.1
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and disruptions to global fire activity

Abstract: Abstract. Future disruptions to fire activity will threaten ecosystems and human well-being throughout the world, yet there are few fire projections at global scales and almost none from a broad range of global climate models (GCMs). Here we integrate global fire datasets and environmental covariates to build spatial statistical models of fire probability at a 0.58 resolution and examine environmental controls on fire activity. Fire models are driven by climate norms from 16 GCMs (A2 emissions scenario) to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
611
1
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 778 publications
(635 citation statements)
references
References 83 publications
21
611
1
2
Order By: Relevance
“…Statistical models have been used to examine the potential trajectory of changes in fire during the 21st century (e.g. Moritz et al, 2012;Settele et al, 2014). Such models essentially assess the possibility of fire occurring given climate conditions and fuel availability (fire risk or fire danger) based on modern-day relationships between climate, fuel, and some aspects of the fire regime such as burnt area.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical models have been used to examine the potential trajectory of changes in fire during the 21st century (e.g. Moritz et al, 2012;Settele et al, 2014). Such models essentially assess the possibility of fire occurring given climate conditions and fuel availability (fire risk or fire danger) based on modern-day relationships between climate, fuel, and some aspects of the fire regime such as burnt area.…”
Section: Introductionmentioning
confidence: 99%
“…The strong interannual correlation between forest fire activity and fire-season fuel aridity, as well as observed increases in vapor pressure deficit (VPD) (9), fire danger indices (10), and climatic water deficit (CWD) (11) over the past several decades, present a compelling argument that climate change has contributed to the recent increases in fire activity. Previous studies have implicated anthropogenic climate change (ACC) as a contributor to observed and projected increases in fire activity globally and in the western United States (12)(13)(14)(15)(16)(17)(18)(19), yet no studies have quantified the degree to which ACC has contributed to observed increases in fire activity in western US forests.…”
mentioning
confidence: 99%
“…Frequent, gentle fires would consume litter, lower carbon inputs to soil, and, because of their frequency tend to homogenize soil organic matter across landscapes by preventing large buildups of dead organic matter aboveground. The high diversity among mature stands of the Siskiyous is not possible to relate to management, as those stands originated from severe wild fires set by EuroAmercans, an unfortunate combination of unnatural and unmanaged, and a situation that may not be uncommon if, as predicted, climate change results in more frequent, severe wildfires [69].…”
Section: Landscape Legaciesmentioning
confidence: 99%